2013
DOI: 10.1002/grl.50475
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir “snakes” and electrostatic decay in the solar wind

Abstract: [1] When Langmuir waves are driven by an electron beam to large amplitudes, they can undergo electrostatic (ES) decay to smaller wave numbers via a series of backscatters. Truncated ES decay, where the number of backscatters is reduced due to damping, is modeled here using the three-dimensional ES Zakharov equations. Langmuir beats develop in "snake"-like structures parallel to the electron beam direction and are most evident when decay is truncated to a single backscatter. From these results, an analytic form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In Graham et al [2013], the split spectral peak events were shown to be generally consistent with ES decay. We now compare the observed P S and P L with the weak turbulence predictions for ES decay.…”
Section: One-dimensional Split Spectral Peak Eventsmentioning
confidence: 88%
See 2 more Smart Citations
“…In Graham et al [2013], the split spectral peak events were shown to be generally consistent with ES decay. We now compare the observed P S and P L with the weak turbulence predictions for ES decay.…”
Section: One-dimensional Split Spectral Peak Eventsmentioning
confidence: 88%
“…So for large k b , the number of backscatters can be truncated to a small number without a condensate forming [e.g., Robinson et al, 1992;Graham et al, 2013]. So for large k b , the number of backscatters can be truncated to a small number without a condensate forming [e.g., Robinson et al, 1992;Graham et al, 2013].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, the spectrum of E L parallel to B has a single peak. The angle between B and the solar wind velocity is θ Bv =71°, and the predicted Doppler‐shifted frequency difference is ∼300Hz, so if decay was occurring we expect to see distinct spectral peaks near f p [ Graham et al , ; Graham and Cairns , ].…”
Section: Examples Of Harmonic Wavesmentioning
confidence: 99%
“…Density perturbations play a major role in the processes considered to date, including refraction and scattering of Langmuir waves by density fluctuations [3], stochastic growth effects [4], and also nonlinear wave-wave processes such as electrostatic (ES) decay [5][6][7]. Some Langmuir waves exhibit periodic beating consistent with ES decay [7][8][9][10]. However, Langmuir waves often appear localized with typical length scales of $ð10 2 -10 3 Þ D [11][12][13][14].…”
mentioning
confidence: 99%